Four festival concerts in Halle. Second concert, February 18, 1941 - Wiener Philharmoniker::::::::::::::: (Germany; Halle, 2020)
Program for the second concert of the concert series, on Feb. 18, 1941 by the Vienna Philharmonic, conducted by Hans Knappertsbusch, at the great room of the Stadtschützenhaus in Halle, sponsored by the German Labor Front. The program included Beethoven's Seventh Symphony, op. 92. Swastika emblem of the Nazi party printed on cover page.